Charlie and the chocolate factory [Charlie a továreň na čokoládu anglicky]. [book 1] - Dahl, Roald, 1916-1990 (Puffin Books, 2016)
Greetings to you, the lucky finder of this Gold Ticket from Mr Willy Wonka! Tremendous things are in store for you! Charlie Bucket's life is about to change forever, thanks to one miraculous moment! Willy Wonka, chocolate maker extraordinaire, has hidden five golden tickets in five ordinary bars of chocolate, and any child who finds one will get the chance to visit his incredible factory. And Charlie has found one... But so have... Augustus Gloop - a glutton for chocolateVeruca Salt - a spoiled and selfish bratViolet Beauregarde - a repulsive gum-chewerMike Teavee - a television fiendWith a chocolate river, delectable confectionery and mysterious Oompa Loompas, Mr Wonka's factory is the most wondrous place Charlie has ever seen.